Barnes, Washington County - Tanner, Caroline (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author creates a charming portrait of the town of Barnes, Kansas. She uses documents as well as oral interviews to tell the delightful history of the town.
Caroline Tanner, “Barnes, Washington County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/77.
Keywords: A.S. Barnes; Barnes Carnival; Church Socials; Baseball; Business District; Washington County